2015
DOI: 10.1111/idh.12169
|View full text |Cite
|
Sign up to set email alerts
|

Effect of gallium aluminium arsenide diode laser therapy on Porphyromonas gingivalis in chronic periodontitis: a randomized controlled trial

Abstract: GaAlAs diode laser irradiation of diseased periodontal pockets at 685 nm and 1.6 J cm seemed to be an effective adjuvant to mechanical instrumentation to treat chronic periodontitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 40 publications
0
8
0
2
Order By: Relevance
“…LLLT also showed some short‐term additional benefits in the reduction in plaque and improvement of the gingival condition, as well as the improvement of the CAL . Alzoman et al also showed statistically significant improvements in BI and CAL, while Slot et al considered that the changes in CAL were “moderate” for the LLLT + SRP group compared to the SRP group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…LLLT also showed some short‐term additional benefits in the reduction in plaque and improvement of the gingival condition, as well as the improvement of the CAL . Alzoman et al also showed statistically significant improvements in BI and CAL, while Slot et al considered that the changes in CAL were “moderate” for the LLLT + SRP group compared to the SRP group.…”
Section: Discussionmentioning
confidence: 99%
“…P values of <.05 were considered significant. The sample size calculation determined that minimum number of subjects was 5 per treatment group, based on previous published study and required parameters: power of study 0.8 and α error probability 0.05, using the change in CAL as a primary outcome variable. Consequently, a sample of 30 subjects per group was included, because some of them may be lost during the study.…”
Section: Methodsmentioning
confidence: 99%
“…Razvoj antibiotske rezistencije kod bakterija izazvao je potrebu za novim, alternativnim metodama lečenja infekcije. U nedavno objavljenim studijama pokazano je da je terapija periodontalnih džepova laserom na bazi galijuma efikasna pomoć u skidanju zubnog plaka I planiranju korena u terapiji i nadzoru parodontopatije [30][31][32] .…”
Section: Potencijalna Aplikacija Galijuma U Prevenciji Gubitka Zubaunclassified
“…The development of antibiotic resistance in bacteria has prompted a great need for new and alternative treatment methods for infection. Recent studies have been reported that gallium-containing laser therapy of diseased periodontal pockets seemed to be an effective adjuvant to scaling and root planning in the treatment and management of periodontitis [30][31][32] .…”
Section: Potential Application Of Gallium In Tooth Loss Preventionmentioning
confidence: 99%
“…In addition, diode lasers are inexpensive devices and easy to miniaturize, which has led to the development of a wide range of clinical applications. At high power, diode lasers can be used to perform incision and hemostasis of soft tissue, whereas at low power, they can be used for periodontal therapy and treatment of hypersensitivity and temporomandibular disorders . Low‐power laser irradiation has been proposed as a treatment (low‐level laser therapy; LLLT) to harness the stimulatory effect of light on living tissues.…”
Section: Introductionmentioning
confidence: 99%